EXPERIMENTAL STUDY ON SUPPER-HIGH PRESSURE FLUIDS IN THE UPPER MANTLE USING DIAMOND ANVIL CELL - Hu S.; Zhang R.; Zhang X. (My University, 2006)
The deep earth fluids compose mainly NaCl-H2O. The properties of the earth fluids are getting to change with their locations in the different depth, form low temperature and pressure in the shallow to high temperature and pressure in the deeper parts of the earth. Fluids of NaCl-H2O lie in the deeper parts always presented in a supercritical state of water. As the fluids rose from deeper parts to shallow, they would go through the critical state, and to a state of lower than the critical point of water due to decreasing temperatures and pressures. The best method for in situ observation of the deep earth fluids is to utilized a hydrothermal diamond anvil cell (HDAC)connected to different spectrometers, and by using Synchrotron radiation technique. Authors performed a study of Infrared spectra of NaCl-H2O solution at 10GPa by using diamond anvil cell and connected to Infrared spectrometer by using synchrotron radiation light source, and a study of infrared spectra of NaCl-H2O solutions by using HDAC connected to FT-IR microscope in the conditions of 3GPa650°. Our method about measurements of infrared spectrometer for NaCl-H2O at high temperatures and pressures provides the data of temperature, pressure and volume of the tested fluids, thus the equation is the state of the fluids can be figure out. The spectra of NaCl-H2O solutions indicated that the vibration frequencies of water molecules are affected by temperatures and pressures. Increase of pressures lead the vibration frequency of water molecules change to low wave numbers. In oppositely, increase of temperatures would derive their vibration frequencies to high wave numbers. In opposite of the effects on water (or crystals) with respect to increasing temperature, increasing pressure at ambient temperature will lead to compress water molecules and crystals, thus the crustal will go to a crystal structure close accumulate. Water at high temperatures and pressures will behave V-L-S phases, the critical state, and a supercritical fluid phase. The hydrogen-bond of inter-water molecules will be weaken and broken as close to the critical state of water.
Keywords: HIGH TEMPERATURE AND SUPER-HIGH PRESSURE FLUIDS; HYDROGEN BOND; INFRARED SPECTRA OF HIGH PRESSURE AND TEMPERATURE AQUEOUS SOLUTIONS; NACL-H; SUPERCRITICAL STATE; SYNCHROTRON RADIATION LIGH SOURCE; DEEP EARTH